2019
DOI: 10.1182/blood-2018-04-845420
|View full text |Cite
|
Sign up to set email alerts
|

Acute myeloid leukemia induces protumoral p16INK4a-driven senescence in the bone marrow microenvironment

Abstract: Acute myeloid leukemia (AML) is an age-related disease that is highly dependent on the bone marrow (BM) microenvironment. With increasing age, tissues accumulate senescent cells, characterized by an irreversible arrest of cell proliferation and the secretion of a set of proinflammatory cytokines, chemokines, and growth factors, collectively known as the senescence-associated secretory phenotype (SASP). Here, we report that AML blasts induce a senescent phenotype in the stromal cells within the BM microenvironm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 44 publications
5
66
0
Order By: Relevance
“…alterations, as is the case for the Shwachman-Bodian-Diamond syndrome gene, remodeling of the niche by malignant myeloid cells (16,25), or environmental exposures such as cytotoxic therapy, as suggested by this study. We hypothesize that MSCs in the BM microenvironment are key players, because recipient mice were lethally irradiated, leading to cell death of immune cells but not the MSCs, which are typically radioresistant.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…alterations, as is the case for the Shwachman-Bodian-Diamond syndrome gene, remodeling of the niche by malignant myeloid cells (16,25), or environmental exposures such as cytotoxic therapy, as suggested by this study. We hypothesize that MSCs in the BM microenvironment are key players, because recipient mice were lethally irradiated, leading to cell death of immune cells but not the MSCs, which are typically radioresistant.…”
Section: Discussionmentioning
confidence: 51%
“…20). MSCs isolated from patients with MDS and AML display several characteristic features of senescence, including TP53 pathway activation (21,22), increased senescence-associated β-galactosidase (SA-β-gal) expression (22)(23)(24), and upregulation of senescence-associated secretory phenotype (SASP) factors, such as IL6 (25,26). Moreover, AMLs can induce a senescent phenotype in bone marrow (BM) stromal cells, and targeting these senescent cells improves the survival of mice with leukemia (25), illustrating the importance of a senescent microenvironment in the pathophysiology of leukemia.…”
mentioning
confidence: 99%
“…These have highlighted differences in morphology [7], growth rate [27,39], altered osteogenic or adipogenic differentiation capacity [14,27,29,40], altered methylation signatures [27], and altered ability to support normal hematopoietic stem and progenitor cells [7,27]. Some have found altered senescence [41] whereas others have not [39]. Other groups have also shown that at earlier passages, AML-MSCs have slower growth rates but that by passage 3, doubling times are equivalent to ND-MSCs [27].…”
Section: Discussionmentioning
confidence: 99%
“…AML-MSCs have been found to have increased expression of FABP4 in comparison with normal controls and delayed osteogenic potential [29]. They have also been found to have higher lipoprotein lipase expression and lower E-cadherin expression [41]. In 64 AML patients, 41 untreated, Geyh et al [27] found reduced osteogenic differentiation potential with decreased expression of osteocalcin and osterix.…”
Section: Discussionmentioning
confidence: 99%
“…However, the increase in senescent cells with age and a chronic SASP are now known to be key drivers of many pathological hallmarks of aging, including chronic inflammation, tumorigenesis, impaired stem cell renewal, and others (Neves et al, 2015;Tominaga, 2015). Using either or both of two transgenic mouse models that allow the selective elimination of senescent cells (Baker et al, 2011;Demaria et al, 2014), or compounds that mimic the effect of these transgenes, data from several laboratories strongly support the idea that the presence of senescent cells drives multiple age-related phenotypes and pathologies, including age-related atherosclerosis , osteoarthritis (Jeon et al, 2018), cancer metastasis and cardiac dysfunction (Baar et al, 2017;Demaria et al, 2017), myeloid skewing in the bone marrow (Abdul-Aziz et al, 2018;Chang et al, 2016), kidney dysfunction (Valentijn et al, 2018), and overall decrements in healthspan .…”
Section: Introductionmentioning
confidence: 99%